Faktor Risiko Kejadian Tuberculosis Paru Di Wilayah Kerja Puskesmas Rumbai Kecamatan Rumbai Pesisir Tahun 2019 : kejadian Tuberculosis - Nisaulhusna Nisa Ul husna; Suharmadji Suharmadji; Wulan Sari; Agus Alamsyah; Zulmeriza Rasyid (Jurnal Kesehatan Komunitas, 2020)
Tuberculosis (pulmonary TB) is an infectious disease caused by Mycobacterium Tuberculosis, which can attack the lungs and other organs. Rumbai Community Health Center in Rumbai Coastal District has experienced an increase in lung tuberculosis cases each year with the number in 2018-2019 there were 78 cases (35.8%). The purpose of this study was to determine the risk factors for nutritional status, behavior, contact history, and occupancy density for the incidence of pulmonary tuberculosis. This type of research uses obsevational quantitative methods with case control design. The location of the study was conducted in the Work Area of ​​the Rumbai Puskesmas in the Rumbai Coastal District in June-July 2019. The population of this study were some patients with pulmonary tuberculosis and non-pulmonary tuberculosis patients who were registered in the medical records of the Rumbai health center. Respondents in this study were 90 respondents conducted by interview and observation to 45 respondents of pulmonary tuberculosis cases and 45 control respondents who were not patients with pulmonary tuberculosis were selected using systematic random sampling technique. Data collection using questionnaires and cross checks. The analysis used was univariate and bivariate analysis with chi-square test with a confidence level of 95%. The results showed that nutritional status (p-value = 0,000, OR = 25,107 CI 95% = 8,268 - 76,245), contact history (p-value = 0,000, OR = 13,000 CI 95% = 4,505 - 37,510) and behavior (p- value = 0.009, OR = 3.532 CI 95% = 1.440 - 8.665) is a risk factor for the incidence of pulmonary tuberculosis. It is recommended to health centers to increase information related to prevention of the occurrence of pulmonary tuberculosis and conduct active surveillance to break the chain of transmission of pulmonary tuberculosis